Estratigrafía del cretácico superior y terciario inferior en el sector norte de la cuenca del putumayo, departamento del caquetá, colombia (1998)
A new scheme of stratigraphic nomenclature is defined formally in the northern portion of the Putumayo basin. The Masaya Formation (new formation) represents the beginning of the Cretaceous sedimentation during the late Cenomanian, exhibiting fluvial deposits that rapidly grade up-section to intertidal deposits. Towards the NE, the unit onlaps the basement progressively, thus being diachronous.  The Las Iglesias Formation (new formation) represents a regional episode of marine flooding during the Turonian and Coniacian, with a maximum flooding surface dated Santonian. After an erosion period that cannibalized Campanian rocks, intertidal sedimentation during the Maastrichtian to Paleocene took place. This is represented by the Rumiyaco Formation, which bears a fluvial member (El Neme) in its lower part.